Drugs and justice: seeking a consistent, coherent, comprehensive view - Battin, Margaret Pabst (Oxford University Press, 2008)
Drugs "across the board" : toward a consistent, coherent, comprehensive view in drug theory, policy, and practice -- How did it come to be this way? : the historical development of drug regulation -- Drug regulatory agencies and the underlying rationales for drug policy -- Core conceptual problems : addiction -- Core conceptual problems : harm (and benefit) -- Dilemmas of drug management and control : case puzzles and studies in conflict -- Toward justice in drug theory, policy, and practice